PENGEMBANGAN VISIBILITAS PEMASARAN UMKM RUMAH KAYU - Supit, Vekky; Dua, Iyam L; Walangitan, Misael Aldo; Kumaat, Arief Perdana (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2026)
The Woloan Wooden House industry in Tomohon City is an export-oriented creative economy asset with high cultural value. Despite having penetrated European and African markets, reliance on conventional marketing methods may limit its growth in the digital era. This conceptual research aims toanalyze the current implementation of digital marketing in the Woloan Wooden House business and formulate development opportunities to expand market reach and promotion effectiveness. Using a descriptive qualitative approach with literature review and secondary data analysis methods, this study formulates three main strategic pillars. First, the optimization of multi-platform Search Engine Optimization (SEO) to exponentially increase the digital visibility of the product. Second, the development of persuasive and adaptive copywriting, including standardization using international languages (English and Chinese) to facilitate global communication. Third, strengthening consistent visual content and branding based on brand guidelines to build consumer trust. The synergy between machine readability and human readability serves as a balanced strategic instrument to reinforce the domestic market share while winning the competition on the global stage.